HUBUNGAN BEBAN KERJA DENGAN MOTIVASI KERJA PERAWAT DALAM MELAKSANAKAN ASUHAN KEPERAWATAN - Silitonga, Erwin; Saragih, Masri; Sipayung, Rosetty (Universitas Prima Indonesia, 2020)
The quality demands of implementing nursing care are greatly influenced by the workload of nurses, the workload of nurses must also be in accordance with the abilities and work motivation of a nurse so that it is in accordance with nursing care standards. This study aims to determine the relationship of workload with nurses' work motivation in carrying out nursing care in the inpatient room of Sari Mutiara Lubuk Pakam Hospital. Descriptive correlation research design with cross sectional study design. The population in this study were all nurses in the inpatient ward with a total of 56 people, the sampling technique used total population. Data analysis using univariate and bivariate analysis with Chi-Square test. The results showed a high workload of nurses 69.6% and motivation of nurses to carry out low nursing care 67.8%. Chi-Square test results there is a relationship of workload with nurse work motivation in implementing nursing care with a p-value of 0.017. Then it can be concluded that the workload has a relationship with the work motivation of nurses in implementing nursing care. It is recommended that the hospital adjust the number of nurses to the number of available patients and pay attention to the performance of nurses in carrying out nursing care.